2001
DOI: 10.1093/nar/29.13.2810
|View full text |Cite
|
Sign up to set email alerts
|

E2F mediates induction of the Sp1-controlled promoter of the human DNA polymerase varepsilon B-subunit gene POLE2

Abstract: The B-subunits of replicative DNA polymerases from Archaea to humans belong to the same protein family, suggesting that they share a common fundamental function. We report here the gene structure for the B-subunit of human DNA polymerase epsilon (POLE2), whose expression and transcriptional regulation is typical for replication proteins with some unique features. The 75 bp core promoter region, located within exon 1, contains an Sp1 element that is a critical determinant of promoter activity as shown by the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…In yeast and human it has been shown that some DNA polymerase ɛ subunits are transcriptionally regulated at the G 1 /S phase transition. For instance, POLE2 is regulated by two E2F–pocket protein complexes (Huang et al. , 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In yeast and human it has been shown that some DNA polymerase ɛ subunits are transcriptionally regulated at the G 1 /S phase transition. For instance, POLE2 is regulated by two E2F–pocket protein complexes (Huang et al. , 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Full lists of genes whose promoters were found to contain high scoring sites for the enriched TFs are provided in Supplemental Tables B1-B8 (available online at www.genome.org.) Chang et al 2001;Huang et al 2001;Nishikawa et al 2001;Parisi et al 2002). As for E2F and NF-Y, co-occurrence of functional binding sites for both TFs was reported in several promoters, including Cdc2, TK, POLA, Cyclin A, and several histone genes (Matuoka and Yu Chen 1999).…”
Section: Discussionmentioning
confidence: 96%
“…The contribution of these Sp1C and D to overall promoter activity is minimal in the presence of the interacting E2F and Sp1A and B sites. E2F-Sp1 interactions important in regulating transcription have also been reported (Lin et al, 1996;Rotheneder et al, 1999;Huang et al, 2001) for other promoters. Moreover, similar to that demonstrated in the case of the cdc25A gene (Chen and Prywes, 1999), on the basis of the supershift obtained in an EMSA using antibody directed against the E2F pocket protein, p107, we were able to more definitively conclude that an interaction between an E2F factor and a noncanonical E2F sequence element occurs in the MRP7 promoter.…”
Section: Discussionmentioning
confidence: 83%
“…Annealing of ss oligomers and electrophoresis conditions were as reported elsewhere (Huang et al, 2001). Ds oligomers were 32 P-end-labeled using the Gel Shift Assay Systems kit from Promega.…”
Section: Electrophoretic Mobility Gel Shift Assaymentioning
confidence: 99%